Use of real-world evidence for healthcare decision-making in the Middle East: practical considerations and future directions. (4th May 2019) - Akhras, Kasem S.; Alsheikh-Ali, Alawi A.; Kabbani, Samer
ABSTRACT: Introduction : Real-world evidence (RWE) is increasingly being used in coverage, reimbursement and formulary decisions for medicines globally. Areas covered : The Middle East (ME) region is significantly behind in generating and using RWE in health policy decisions due to several factors that shaped the health sector over the past few decades. The trend, however, is changing due to several factors that are shaping the future of the healthcare industry in the region. Among other factors, rising healthcare cost, changing population and disease demographics, increased focus on the quality of healthcare, digitization of medical data, increased demand for local clinical and economic data, and overall greater influence of global trends in the healthcare industry. For the region to realize the benefit of RWE in healthcare decisions, it needs to overcome several challenges including embracing the value that RWE brings to healthcare decisions, building trust between stakeholders, establishing reliability and validity of databases used to generate RWE, enhancing technical capabilities, investing in local data generation, and conducting high-quality RWE studies while maintaining patients' confidentiality. Expert commentary : We believe that the next decade will witness significant increase in RWE generation in the region, and will play a key role in driving efficiency in healthcare delivery.